El marketing digital y las ventas en el patio de comida Waysa Pamba, ciudad del Coca, provincia de Orellana - Camacho Seis, Evelyn Lisbeth (2025)
This research arises from a genuine and pressing need in the city of El Coca. It was carried out to support the growth of Waysa Pamba Food Court—a space that not only provides income for Kichwa families, but also showcases Amazonian culture and gastronomy. In an increasingly digital world, small businesses face the challenge of adapting to avoid being left behind. This thesis explores how digital marketing can be a powerful tool to boost sales and visibility for these ventures, which are mostly led by women entrepreneurs from the community. By surveying 30 vendors from the food court, several key issues were identified: a lack of defined digital strategies, low engagement on social media, and limited knowledge of digital tools, paid ads, and influencer marketing. While many already use platforms like WhatsApp, Facebook, or TikTok, a significant number aren’t making full use of their potential. The findings show that most vendors agree digital marketing has helped increase their sales, but there are still gaps in training, technical knowledge, and financial resources. Despite this, the interest and willingness to improve are clearly present. For this reason, the final proposal includes an accessible, realistic, and culturally appropriate strategy: from promotions, videos, and reels on social media, to the use of local influencers and building a strong Amazonian identity in each post—all tailored to the financial realities of these vendors.